“Ask for a Miracle”: Memory, Manipulation, and Displacement in the Cooper-Young Neighborhood - Clevenger, Hannah (Reconceptualizing Educational Research Methodology, 2020)
Through a combination of walking, archival, and arts-based research methodologies, this paper expands the experiential process of creating a visual representation of the changes that have taken place in the Cooper-Young neighborhood of Memphis, Tennessee. Combined, these (visual) elements highlight the disparities between the dominant and hidden narratives of Cooper-Young’s history.